Distinct and redundant roles for zebrafish her genes during mineralization and craniofacial patterning - Stenzel, Amanda; Mumme-Monheit, Abigail; Sucharov, Juliana; Walker, Macie; Mitchell, Jennyfer M.; Appel, Bruce; Nichols, James T. (Frontiers in Endocrinology, 2022)
The Notch pathway is a cell-cell communication system which is critical for many developmental processes, including craniofacial development. Notch receptor activation induces expression of several well-known canonical targets including those encoded by the hes and her genes in mammals and zebrafish, respectively. The function of these genes, individually and in combination, during craniofacial development is not well understood. Here, we investigated zebrafish her9 and her6 gene function during craniofacial development. We found that her9 is required for osteoblasts to efficiently mineralize bone, while cartilage is largely unaffected. Strikingly, gene expression studies in her9 mutants indicate that although progenitor cells differentiate into osteoblasts at the appropriate time and place, they fail to efficiently lay down mineralized matrix. This mineralization role of her9 is likely independent of Notch activation. In contrast, her9 also functions redundantly with her6 downstream of Jagged1b-induced Notch activation during dorsoventral craniofacial patterning. These studies disentangle distinct and redundant her gene functions during craniofacial development, including an unexpected, Notch independent, requirement during bone mineralization.